Biotechnology or organic? Extensive or intensive? Global or local? A critical review of potential pathways to resolve the global food crisis. (February 2016) - Fraser, Evan; Legwegoh, Alexander; KC, Krishna; CoDyre, Mike; Dias, Goretty; Hazen, Shelley; Johnson, Rylea; Martin, Ralph; Ohberg, Lisa; Sethuratnam, Sri; Sneyd, Lauren; Smithers, John; et al.
Abstract: While experts agree that poverty, population, energy prices, climate change, and socio-political dynamics undermine global food security, there is no agreement on effective strategies to meet this challenge. For example, some promote "high tech" solutions (e.g. biotechnology) designed to boost yield while others prefer local food systems. To better understand these debates, this article explores four perspectives from the literature: (1) technology to increase food production; (2) equitable food distribution; (3) policies to reduce pollution and waste; and (4) community action to promote sovereign food systems. The paper concludes with recommendations on how food scientists can navigate these controversies to help research and policy making. Highlights: Experts agree environmental and socio-political changes undermine food security. There is no agreement on best strategies to meet this challenge. This article reviews 4 viewpoints: technology, distribution, sovereignty and policy. Conclusions discuss how food scientists can navigate disagreements.